Methods of Arab TV Programs Production - سبع السنجري بشرى داوود; حميد ايمان عبد الرحمن (ALBAHITH ALALAMI, 2015)
This research investigates the methods of producing Investigative Arabic Television Programs that are able to prove its existence during a short period of time as a form of Television programs on Arab satellite channels growing in number and varied in content. The research aims to present qualitative and quantitative descriptions of the methods used in tackling the topics discussed in the program, and knowing whether they satisfy the conditions and scientific foundations for the research, investigation, analysis, and interpretation. The researcher uses the survey method and uses the tool of content analysis including a set of methodological steps that seek to discover the implied meaning of the research sample represented by the program loops people can watch on Al-Jadeed satellite channel of Lebanon. This is done by the qualitative content analysis of seven loops of the program in terms of shape, type, topic, and the level of its production, types, and its sources. The reason for choosing this topic is that there are few studies that deal with producing of investigative television program mainly in M.A theses and Ph. D dissertations in spite of its importance. The research concludes the following results: 1- The program uses all types of appropriate sources for investigative work. 2- The researcher uses live audio of the program at 42%. It depends on natural sound surrounding the enrolment event followed by music at 31.67% especially for events in which natural sounds are mixed. So, they are replaced by music as they have a significant effect. 3- He relies on Web film site of the event at 45% and this is a proof of the sincerity of the program. 4-The hidden camera style occupies 48.83% which causes a sensation and strong reactions towards this style.